Effects of pressure side film cooling hole placement and condition on adiabatic film cooling effectiveness characteristics of a transonic turbine blade tip. (15th December 2022) - Collopy, Hallie; Ligrani, Phillip M.; Xu, Hongzhou; Fox, Michael
Highlights: Effects of film cooling hole placement location for four different film cooling configurations along the upper pressure side of a transonic squealer are considered. Adiabatic film cooling effectiveness distributions are provided for blowing ratios ranging from 0.42 to 3.20 for squealer blade tip surface, and upper pressure side of the blade. Film effectiveness distributions produced by the different film cooling configurations are vastly different along the squealer blade tip surface, and upper pressure side of the blade. The present investigation is the first to consider the effects of hole placement location for upper pressure side film cooling arrangements with transonic flow conditions. Abstract: The effects of film cooling hole placement location along the upper pressure side of a transonic squealer are considered. The thermal performance of four different film cooling configurations; B1, B2, B3 and B4, are considered using the University of Alabama in Huntsville's SS/TS/WT (supersonic/transonic/wind tunnel) experimental facility and a simulated turbine blade row using a linear cascade. Surface-varying results are provided for both the squealer blade tip surface, and for the upper pressure side of the squealer blade. These results are given for blowing ratios ranging from 0.42 to 3.20 in the form of spatially-resolved and spatially-averaged adiabatic film cooling effectiveness distributions. Because local static pressure variations and gradients vary in a significant manner at different blade locations, coolant accumulations near surfaces (and the associated surface thermal protection and film effectiveness distributions) produced by the different film cooling configurations are vastly different along the squealer blade tip surface. The B1 and B3 film cooling configurations show that substantial magnitudes of adiabatic film cooling effectiveness are present along the pressure side rim and the suction side rim. Also present is a considerable region of locally increased film cooling effectiveness and a wider region of surface protection within the squealer recess region for the B2 film cooling configuration. The contributions are unique because of a deficit of experimental data for film cooled squealer blades which operate with transonic flow, and because the present investigation is the first to consider the effects of hole placement location for upper pressure side film cooling arrangements with transonic flow conditions.